Silicon Alleviates the Disease Severity of Sclerotinia Stem Rot in Rapeseed - Feng, Yuxia; Hu, Yuxin; Fang, Pengpeng; Zuo, Xiangjun; Wang, Jinxiong; Li, Jiana; Qian, Wei; Mei, Jiaqin (Frontiers in Plant Science, 2021)
Sclerotinia stem rot caused by Sclerotinia sclerotiorum is a devastating disease of rapeseed. This study aimed to investigate the role and the mechanism of silicon (Si) in alleviating disease severity of S. sclerotiorum on rapeseed. In the absorption assays, rapeseed absorbed 10-mM K2SiO3 exhibited 86% decrease on lesion size on infected leaves as compared to the controls. In the spray assay, the lesion length on rapeseed stems was reduced by 30.5 32.9% with the use of 100-mM folia silicon fertilizer as compared to the controls. In the pot assay, the lesion length on rapeseed stems was reduced by 34.9 38.3% by using silicon fertilizer as basal fertilizer. In the field assay, the disease incidence and disease index of sclerotinia stem rot were significantly reduced by the use of solid silicon fertilizer, silicon folia fertilizer and, in particular, the application of both, without negative affection on the main agronomic traits and seed quality of rapeseed. Transcriptome sequencing, quantitative RT-PCR and biochemical assays between K2SO4- and K2SiO3-treated rapeseed leaves revealed that, Si promoted the biosynthesis of defense-related substances and enhanced antioxidation and detoxification abilities in rapeseed after infection. This paper concludes that Si can alleviate disease severity of S. sclerotiorum on rapeseed, partially due to the induced defense responses.